SKRINING PERUBAHAN FISIK, PERILAKU SEKSUAL, DAN PSIKOLOGIS PADA WANITA YANG MENGALAMI MENOPAUSE : Screening Physical, Sexual Behavior And Psychological Changes In Women Experienced Menopause - Probowati, Rovica; Andriani Mei Astuti (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2024)
Background Changes in women experiencing menopause often become a problem in their health. This aims of this research is to identify a picture of the changes that occur in women who have experienced menopause. The research design is descriptive. The research population was women aged 45-59 years who had experienced menopause in Cemani village, Surakarta with no nee a total of 50 subjects. Sampling uses cluster sampling. The variable is the changes that occur at menopause. The instrument uses structured interviews and is analyzed using descriptive analysis. The results of the study described severe physical changes (57.8%), moderate changes in sexual behavior (68.9%), and moderate psychological changes (55.6%). It was concluded that menopausal women will experience physical, sexual behavior and psychological changes with severe and moderate modifications. Keywords: Degeneratif; Wowen; Menoupouse; Skrining